Characterizing seabed sediments at contrasting offshore renewable energy sites - Amjadian, Pegah; Neill, Simon P.; Martí Barclay, Vicky (Frontiers in Marine Science, 2023)
Due to the impacts of climate change, there is an urgent need to scale up existing, and develop novel, renewable energy technologies. Although there are many types of renewable energy technology, ocean renewable energy, including established offshore wind, and novel wave and tidal energy converters, offers many opportunities due to the abundance of the resource, availability of sea space, and (for tidal) predictability. However, the extraction of energy from the ocean environment will influence sediment dynamics and morphodynamics at various temporal and spatial scales. Detailed knowledge of seabed properties is also important for device installation, affecting foundation design and cabling. In this study, 36 seabed sediment samples were collected across a region of the Irish Sea extending from the west of Anglesey into Liverpool Bay up to a maximum distance of around 35 km offshore – a region where there are many existing and planned ocean renewable energy projects. Particle size analysis at quarter phi intervals was used to calculate the statistical properties of the seabed sediment samples, including Mean grain size, Sorting, Skewness and Kurtosis. These properties were compared against the outputs of wave (SWAN) and tidal (TELEMAC) models of the region to investigate the relationship between environmental variables and sediment characteristics, and to determine the impact and challenges of renewable energy technologies deployed in the region. Most of the sediments in the study area are medium sand, polymodal, very poorly sorted, coarse skewed, and very platykurtic. We found that mean water depth and peak current speed have the largest influence on Median grain size, and Sorting can be affected by tidal range, in addition to water depth and peak current speed. Moreover, minimal influence of wave climate was found on the sediments. A thorough discussion based on a literature review of the environmental issues of various energy converters (tidal energy converter (both individual and arrays), tidal barrage/lagoons, and wind turbines) was used to determine how devices in the study region, and at other sites throughout the world, would interact with sediment dynamics. We make recommendations on ways to minimize environmental impacts of ocean energy technologies.